1963
DOI: 10.1063/1.1733526
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Facile Approximation for Vibrational Energy-Level Sums

Abstract: Some exact sums of harmonic vibrational-energy-level densities for 45 molecules were obtained at various energies with a digital computer. An improved ``corresponding vibrational states'' type of approximation to these sums at low and moderate energies is described. The approximation has the great advantage or being very rapid, of requiring scarcely any calculational detail and of using the actual molecular frequencies. The agreement of the approximation with a smoothed true count is usually within a few perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
160
0
2

Year Published

1964
1964
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(167 citation statements)
references
References 10 publications
5
160
0
2
Order By: Relevance
“…2 ͑which was based upon the Whitten-Rabinovitch expression͒ 34 is the total and not the symmetry accessible density of vibrational states. In general, for two states to couple by anharmonic interaction, they must be close in energy, have the same J-value, be of the same parity and symmetry with respect to exchange of identical nuclei, and have the same l quantum number.…”
Section: H 2 Results-density Of States Analysismentioning
confidence: 99%
“…2 ͑which was based upon the Whitten-Rabinovitch expression͒ 34 is the total and not the symmetry accessible density of vibrational states. In general, for two states to couple by anharmonic interaction, they must be close in energy, have the same J-value, be of the same parity and symmetry with respect to exchange of identical nuclei, and have the same l quantum number.…”
Section: H 2 Results-density Of States Analysismentioning
confidence: 99%
“…It should be stressed that this covers a very important region of the spectrum, since there is extensive empirical evidence to suggest that, for multidimensional molecular systems, the classical approximation to the density of states will be accurate once the sum of states has climbed to this order of magnitude. 4,[33][34][35] Hence, evaluation of the classical trace in Eq. ͑2͒ is likely to prove quite acceptable at higher energies.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, analytic formulas for the density of states of collections of classical oscillators and rotors can be derived and have been the staple in unimolecular rate theory for many years. [32][33][34][35] The quantum mechanical trace in Eq. ͑1͒ is most readily carried out for separable Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to protein dissociation, the rate constants at low internal energy were found to be larger than the corresponding BS results by orders of magnitude as reported. The fact that some parameters used in calculation proposed by Whitten and Rabinovitch [21] were not adequate for proteins at low internal energy was found to be responsible for the overestimation. Improvement [27] of these parameters using the frequency set obtained in our previous work reduced the error to a factor Ͻ 2.…”
mentioning
confidence: 94%
“…Direct counting of states [17][18][19] was attempted from the early days of study together with the computationally less demanding version of using grouped frequencies [20] and approximate methods such as the Whitten-Rabinovitch (WR) semiclassical method [21] and the steepest-descent method [22]. It was observed that all the approximate methods provided erroneous results at low internal energy [4,20,23].…”
mentioning
confidence: 99%